AB0881 Association of rs12218 polymorphism in saa1gene with lumbar spine syndesmophytes in the russian ankylosing spondylitispopulation. a pilot study. (12th June 2018) - Krylov, M.; Erdes, S.; Starkova, A.; Samarkina, E.; Guseva, I.; Konovalova, N.; Varlamov, D.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease from the group of spondyloarthritis (SPa). Earlier studies showed a correlation between SAA1 gene polymorphism, encoding serum amyloid A, and the development of secondary AA-amyloidosis in familial Mediterranean fever and rheumatoid arthritis in Caucasian and Asian populations. The Moriguchi et al (2005) study showed that the −13 T/C polymorphism in the gene 5'-flanking region (rs12218) is a better marker of AA-amyloidosis than mapping of polymorphisms in SAA1 exon 3 (SAA1.1 and SAA1 1.3). Data on rs12218 polymorphism contribution into predisposition to AS and its clinical phenotypes are very scarce. One of the clinical phenotypes, determining the severity of spine damage, is associated with presence of syndesmofytes (SM) in the lumbar (SMl), thoracic (SMt) and cervical (SMc) spine, confirmed by x-ray data. Objectives: To study potential associations of rs12218 polymorphism in SAA1 gene with AS and phenotypes of radiographic progression, with the presence of SMl, SMt and SMc, and correlation with BASDAI, BASFI and ASAS indices. Methods: rs12218 polymorphism was studied in 112 subjects: 47 AS patients (37 males and 10 females, mean age 40y, mean disease duration 213 weeks, mean age at onset 22y, positive for HLA-B27), and 65 healthy volunteers (controls). Genotyping was performed using allele-specific polymerase chain reaction in real time (PCR-RT). Results: The Pearson Correlation analysis showed negative correlation between rs12218 polymorphism and presence of SMl, as well as BASDAI, BASFI scores (r=−0.39, r=−0.35 and r=−0.36, p=0.006, p=0.017, p=0.014, respectively). There were no correlations between rs12218 and pts' age, AS duration and pts' age at AS onset. There were similar rs12218 allele distribution rates between AS patients and the controls. rs12218C allele rates were significantly higher in SMl group (n=23) compared to subjects without SMl (n=24) [50.0% vs. 15.2%, p=0.001]. No association was established between C allele and presence of SM in other parts of the spine. A correlation between BASDAI and BASFI scores and SAA1 gene rs12218 polymorphism was established. Mean BASDAI score was significantly higher in carriers of TC and CC genotypes compared to carriers of TT genotype (5.6±1.3 vs. 3.9±2.3, p=0.004). The mean BASFI scores in carriers of the respective genotypes were (6.1±2.3 vs 4.1±2.8, p=0.012). No significant correlation was found between rs12218genotypes and mean ASDAS score values. Conclusions: Therefore, this pilot study is the first to show the possible participation of rs12218 polymorphism in SAA1 gene in AS pathogenesis in Russian population. We suggest that C allele may be is a risk factor predisposing to SMl [OR 5, 14 95% CI(1.75–16.17), p=0.001]. The data obtained on a limited sample of patients require further validation on larger samples of patients involving different population groups. Disclosure of Interest: None declared